The Impact of The Pandemic on the Informal Eating Out Habits of Filipino Diners in Dubai, United Arab Emirates - Campaner, Jonnicko P.; Ramos, Allan Clavin J. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study assessed the effect of the pandemic on the informal eating habits of Filipino diners in Dubai, United Arab Emirates, according to the following dimensions: dining experience, online food orders, takeaway orders, marketing promotion, and brand loyalty. The main instrument used in the study to collect data is an online questionnaire made by the researcher. The researcher created an online survey questionnaire using Google Forms and disseminated it through Facebook, Messenger, and email. A total of 414 surveys were answered. The acquired data were analyzed, synthesized, and statistically treated. The major goal of this study is to design and facilitate a program that will aid Dubai, United Arab Emirates restaurant owners, and leaders who are members of the Philippine Business Council in Dubai and the Northern Emirates in getting Filipino diners back into the dining scene and increasing their profitability. The researcher's recommendation is to host a conference with the theme "Catering to the Filipino Palate: Enhancing the Dining Experience in Dubai" to assist restaurants in customizing their offerings and services to Filipino customers' needs (the dining experience), to enhance restaurants' online ordering systems, and to maximize takeaway orders. (Order Food Online), to provide insights on how restaurants may develop successful marketing strategies and promotions to draw in and keep consumers (Marketing Promotions), and to emphasize the value of upholding one's principles and heritage while serving a wide range of diners.